Let-7 Represses Carcinogenesis and a Stem Cell Phenotype in the Intestine via Regulation of Hmga2. - Blair B Madison; Arjun N Jeganathan; Rei Mizuno; Monte M Winslow; Antoni Castells; Miriam Cuatrecasas; Anil K Rustgi (PLoS Genetics, 2015)
Let-7 miRNAs comprise one of the largest and most highly expressed family of miRNAs among vertebrates, and is critical for promoting differentiation, regulating metabolism, inhibiting cellular proliferation, and repressing carcinogenesis in a variety of tissues. The large size of the Let-7 family of miRNAs has complicated the development of mutant animal models. Here we describe the comprehensive repression of all Let-7 miRNAs in the intestinal epithelium via low-level tissue-specific expression of the Lin28b RNA-binding protein and a conditional knockout of the MirLet7c-2/Mirlet7b locus. This ablation of Let-7 triggers the development of intestinal adenocarcinomas concomitant with reduced survival. Analysis of both mouse and human intestinal cancer specimens reveals that stem cell markers were significantly associated with loss of Let-7 miRNA expression, and that a number of Let-7 targets were elevated, including Hmga1 and Hmga2. Functional studies in 3-D enteroids revealed that Hmga2 is necessary and sufficient to mediate many characteristics of Let-7 depletion, namely accelerating cell cycle progression and enhancing a stem cell phenotype. In addition, inactivation of a single Hmga2 allele in the mouse intestine epithelium significantly represses tumorigenesis driven by Lin28b. In aggregate, we conclude that Let-7 depletion drives a stem cell phenotype and the development of intestinal cancer, primarily via Hmga2.